Comparing central and Eastern European mass shootings to American mass shootings - Anisin, Alexei (International journal of comparative and applied criminal justice, 2023)
This study puts forward the first analysis of mass shootings that occurred in Central and Eastern European countries and compares them to American mass shootings. Qualitative comparative analysis is utilised to assess whether pathways of explanatory conditions are similar or different according to two samples of cases featuring 76 shootings that occurred in Central and Eastern European states and 103 that occurred in the United States. Results reveal six pathways that account for the former sample and nine for the latter. American mass shootings are more causally complex and are associated with mental illness, ideological motivations, and grievances against groups and institutions to a greater extent. American mass shootings are also more lethal, while the average age of perpetrators of both US and CEE mass shootings is around 34 years old.